2022
DOI: 10.3390/su142013069
|View full text |Cite
|
Sign up to set email alerts
|

Market-Specific Barriers and Enablers for Organizational Investments in Solar PV—Lessons from Flanders

Abstract: Solar Photovoltaics (PV) is an important contributor to a sustainable energy transition and consists of an increasingly affordable and accessible technology. Although solar PV policies in industrialized countries have mainly benefited affluent households, non-homeowner market segments often remain underdeveloped. In this paper, we review barriers and enablers for solar PV investments in non-homeowner market segments and investigate sustainability aspects of its institutional environment. We use focus group dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Recent survey research focuses on barriers and enablers to increase self-consumption (and thus increase the economic benefits) of solar PV production (Colasante et al, 2022), including motivations for battery energy storage adoption (Alipour et al, 2022) or behavioral change (Colasante et al, 2021). Research on solar PV investments in non-residential market segments is far more limited and utilizes qualitative research techniques such as interviews (Reindl and Palm, 2021) and focus groups (Van Opstal and Smeets, 2022a).…”
Section: Literaturementioning
confidence: 99%
“…Recent survey research focuses on barriers and enablers to increase self-consumption (and thus increase the economic benefits) of solar PV production (Colasante et al, 2022), including motivations for battery energy storage adoption (Alipour et al, 2022) or behavioral change (Colasante et al, 2021). Research on solar PV investments in non-residential market segments is far more limited and utilizes qualitative research techniques such as interviews (Reindl and Palm, 2021) and focus groups (Van Opstal and Smeets, 2022a).…”
Section: Literaturementioning
confidence: 99%
“…The advantage of this mixed-method approach is that it combines the analytic rigor of multivariate statistical analysis techniques with qualitative techniques that fully consider the undocumented and implicit knowledge of stakeholders in a descriptive way [176]. Focus group research within the domain of circular economy research has been used to gain an in-depth understanding of value propositions and boundary conditions for the implementation of circular business models and circular economy strategies [177][178][179][180][181]. A mixed-method approach has been applied to circular economy challenges, such as stakeholder awareness [182], reverse logistics [183], and organisational implementation practices [184].…”
Section: Survey and Focus Group Researchmentioning
confidence: 99%
“…Sheng and Liu [12] suggested that residential solar development needs cooperation among political, market, and community actors. Some researchers found challenges associated with renewable energy [1,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%